Investigation of the Thermal Stability of a Solar Absorber Processed through a Hydrothermal Technique - S. A. Abdullahi; R. Akoba; J. Sackey; S. Khamlich; S. Halindintwali; Z. Y. Nuru; M. Maaza (Solar, 2022)
In this work, we study the thermal stability of a hydrothermally treated stainless steel (SS) selective solar absorber by annealing in air in a temperature range between 300 °C and 700 °C for a soaking time of 2 h. Thermal stability testing in the presence of air is critical if the vacuum is breached. Therefore, the SS was characterized by X-ray diffraction (XRD), mechanical, and optical techniques. The XRD analysis shows that the grain size of the as-treated absorber is 67 nm, whereas those of the annealed absorbers were found to be in the range between 66 and 38 nm. The phase of the as-treated and annealed SS was further identified by XRD as Fe2O3. The EDS result shows that the elemental components of the SS were C, Cr, Fe, and O. The strain (ε) and stress (σ) calculated for the as-treated absorber are 1.2 × 10−1 and −2.9 GPa, whereas the annealed absorbers are found in the range of 4.4 × 10−1 to 5.2 × 10−1 and −121.6 to −103.2 GPa, respectively, at 300–700 °C. The as-treated SS absorbers exhibit a good spectra selectivity of 0.938/0.431 = 2.176, which compares with 0.941/0.403 = 2.335 after being annealed at 300 °C and 0.884/0.179 = 4.939 after being annealed at 700 °C. These results indicate a small improvement in absorptivity (0.941) and emissivity (0.403) after annealing at 300 °C, followed by a significant decrease after annealing at 700 °C. The obtained analysis confirms that the annealed SS absorber exhibits excellent selectivity and is suitable to withstand any thermal condition (≤700 °C) in air. Thus, using a cost-effective approach as demonstrated in this study, the as-treated and annealed SS absorber could be used for photo-thermal conversion applications.